THE CONCEPT "SINN DES LEBENS" IN PHILOSOPHY AND PSYCHOLOGY - V. Y. Popov; Е. V. Popova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The paper considered the explication of the concept of "Sinn des Lebens" within the framework of Western philosophy and psychology of the ХІХ-ХХІ centuries. On the basis of this, the role of this concept in contemporary theoretical discussions and psychological and psychotherapeutic practices is understood. Theoretical basis. The authors believe that understanding the concept of "Sinn des Lebens" is possible only based on the synthesis of modern analytical philosophy methods with the methodological guidelines of modern psychology, in particular logotherapy. Originality. The authors have proved that the problem of "meaning of life" is not an "eternal problem" of philosophy, but arises only in the early nineteenth century as a reflection on European secularization and widespread individualistic values and becomes extremely relevant gaining different interpretations at the beginning of the twentieth century based on the crisis of the sensory values of modern man. Conclusions. The concept of "Sinn des Lebens" originated in the philosophy of the German Romantics and gained philosophical significance only in the works by Schopenhauer, Kierkegaard and Nietzsche. Russian philosophy and literature (especially L. Tolstoy) give priority to the meaning of life in ethical and anthropological studies, focusing on its religious intentions. Analytical philosophy and existentialism appear to be diametrically opposed to the life-purpose anthropological problems, but they attempt to solve this problem by understanding the absurdity of human existence and language from different angles of view. The most reasonable concept of meaning in psychology can be considered Frankl’s logotherapy, which, despite certain drawbacks, remains the most significant in modern Western psychology. Modern philosophical studies on the problems of the meaning of life, despite their prudent analyticity and systematic nature, have not found credible criteria and means of human life self-reflection yet and have further incentives to develop their methodological and philosophical considerations. However, the diversity of interpretations of the concept of "meaning of life" that exists in modern scientific literature needs further reflection.